2012
DOI: 10.4067/s0718-27242012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Factors that Affect the University-Industry Technology Transfer Processes of a Private University

Abstract: This case study researched organizational factors that affect the university-industry technology transfer (UITT) processes of a private university, chosen by its success and uniqueness in the Brazilian context. Stood out as factors: innovation among pillars of management; valuing of research and intellectual property; qualified students, teachers and managers; multidisciplinary research groups; stability of governing body; performance of the TTO, Technology Management Agency and Technology Park. Difficulties h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
7
1
1
Order By: Relevance
“…It is assumed that these motivations have been necessary in order for scientists to overcome obstacles to the UITT process in Brazil which, being recent, still faces a series of cultural, legal and procedural barriers Closs et al, 2012a). In opposition to the aforementioned motivations, the motivational types conformity, tradition and security, whose motivational goals involve the search for stability and preserving the status quo (Tamayo and Paschoal, 2003), were not identified in the present study.…”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…It is assumed that these motivations have been necessary in order for scientists to overcome obstacles to the UITT process in Brazil which, being recent, still faces a series of cultural, legal and procedural barriers Closs et al, 2012a). In opposition to the aforementioned motivations, the motivational types conformity, tradition and security, whose motivational goals involve the search for stability and preserving the status quo (Tamayo and Paschoal, 2003), were not identified in the present study.…”
Section: Discussioncontrasting
confidence: 45%
“…Difficulty balancing time between research, the patenting process and teaching is a deterrent for Brazilian researchers (Santana and Porto, 2009;Closs et al, 2012a). Caldera and Debande (2010) found that regulations addressing such conflicts of interest favored university participation in R&D and Only by partnering with companies.…”
Section: Methodological Proceduresmentioning
confidence: 99%
See 3 more Smart Citations